Solid acid catalysts, processes for their preparation and use

CN117917275BActive Publication Date: 2026-10-30CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202211289627.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-10-20
Publication Date
2026-10-30
Estimated Expiration
2042-10-20

AI Technical Summary

Technical Problem

[0008]本发明的目的是为了克服现有技术存在的固体酸催化剂中强酸中心较少,酸性分布弥散,应用于复杂原料的转化率有待进一步提高的问题,提供一种固体酸催化剂及其制备方法和应用

Benefits of technology

[0020]本发明提供的固体酸催化剂采用高价金属改性的硅铝分子筛与金属活性组分以及硫酸根离子相配合,且具有集中的强酸分布特性及选择性加氢功能,用于复杂烃类原料的芳烃转化反应,具有反应活性高及产物选择性高的优势。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0003900952790000161
    Figure BDA0003900952790000161
  • Figure BDA0003900952790000162
    Figure BDA0003900952790000162
  • Figure BDA0003900952790000171
    Figure BDA0003900952790000171
Patent Text Reader

Abstract

The application relates to the field of catalysts, and discloses a solid acid catalyst and a preparation method and application thereof. The solid acid catalyst contains a high-valence metal modified silicon-aluminum molecular sieve, a metal active component and sulfate ions; the high-valence metal is selected from metals with a valence of +2 or more; the metal active component is selected from at least one of metal elements in groups IVB, VB, VIB, VIIB and VIII; and in the catalyst, the proportion of the amount of strong acid with a desorption temperature of more than 400 DEG C in the total acid amount is more than 60% according to the NH3-TPD desorption amount. The solid acid catalyst has the advantages of concentrated strong acid distribution characteristics and selective hydrogenation function, and when the catalyst is used in an aromatic hydrocarbon conversion reaction of a complex hydrocarbon raw material, the catalyst has the advantages of high reaction activity and high product selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of catalysts, specifically to a solid acid catalyst, its preparation method, and its application. Background Technology

[0002] Molecular sieves, with their regular channels, abundant acid centers, and large specific surface area, are ideal materials for acid-catalyzed reactions and are widely used in petrochemical hydrocarbon conversion processes. ZSM-5, MOR, Beta, and Y molecular sieves have been extensively studied and have achieved large-scale industrial applications in catalytic cracking, hydrocracking, isomerization, alkylation, disproportionation, and alkyl transfer reactions. Typically, molecular sieves synthesized in a single step are non-acidic sodium-type sieves. They require ion exchange with ammonium salts or protic acids at specific temperatures and high-temperature calcination to exhibit acidity. However, molecular sieve materials often suffer from uneven acid strength distribution. Excessive acidity can exacerbate side reactions such as deep cracking and coking within the sieve channels, while weak acid centers can lead to low conversion rates and high reaction temperatures in processes with high activation energies. Furthermore, high-temperature calcination often causes the collapse of the molecular sieve channel structure, hindering the reaction process. Modulating the acidity of molecular sieves by exchanging different cations with them and improving their structural stability is an important method for molecular sieve modification. For example, CN102806097B discloses a rare-earth-containing Y-type molecular sieve cracking catalyst and its preparation method. The NaY molecular sieve is first shaped and calcined, then subjected to ammonium exchange, followed by a second calcination and rare-earth ion exchange. This yields a rare-earth-containing Y-type molecular sieve cracking catalyst with a large total pore volume and specific surface area. CN103159227B discloses a magnesium-modified ultrastable rare-earth Y-type molecular sieve and its preparation method. This method uses NaY molecular sieve as raw material, performs rare-earth exchange reaction and dispersion pre-exchange reaction, then undergoes ultrastable calcination treatment, and finally undergoes magnesium ion exchange modification. The above patents mainly inhibit dealuminization of the molecular sieve framework and improve the structural stability of the molecular sieve through rare-earth modification, and weaken the acidity within the molecular sieve channels through the exchange of second elements such as magnesium, thereby inhibiting the deep cracking process. However, none of them involve improving the acid strength within the molecular sieve channels through ion exchange.

[0003] To improve the low-temperature reaction activity of catalysts, the development of solid superacids with high acid strength has become a research hotspot in recent years. Commonly used superacid catalysts include sulfated ZrO2, TiO2, Fe2O3, and Al2O3. In addition, composite metal oxides such as MoO3 / ZrO3 and WO3 / ZrO2 also exhibit strong acidity. Solid superacid catalysts have acid strength exceeding that of molecular sieve catalysts and exhibit good low-temperature activity and selectivity for hydrocarbon conversion reactions such as dealkylation and isomerization. However, existing solid superacid catalysts generally suffer from low pore volume and specific surface area, leading to low catalyst conversion efficiency. To overcome these problems, molecular sieves have been combined with solid superacids, and solid superacid catalysts supported on molecular sieves or alumina have been further synthesized.

[0004] CN108328624B discloses a modified Beta molecular sieve, its preparation method, and its application. The method includes a step of steam-modifying a hydrogen-type β molecular sieve, and loading the steam-modified hydrogen-type β molecular sieve with zirconium sulfate to obtain the modified β molecular sieve. This method overcomes the disadvantages of traditional ion exchange resins, such as difficulty in regeneration, easy loss of active components in heteropolyacid and solid superacid catalysts, and low activity and selectivity of currently reported catalysts such as β molecular sieves, HY molecular sieves, and mordenite.

[0005] CN103041843A discloses an isomerization catalyst composition and its application. The composition involves supporting rare earth oxides on mordenite to obtain modified mordenite, using a mixture of sulfur-containing compounds and inorganic oxides as a binder, and then loading noble metal elements from group VIII and metal additives. The catalyst is used in the isomerization process of C4-C12 alkanes to produce high-octane gasoline components.

[0006] CN101209423A discloses a method for preparing a superacid molecular sieve catalyst, which involves mixing a solution of one or more modified components selected from elements of the IIIA, IVA, IIIB, IVB, La series, and Ac series with a suspension of molecular sieve, aging, filtering, drying, and calcining to obtain a molecular sieve catalyst with superacidity, which can be applied to alkylation reaction processes.

[0007] However, none of the aforementioned patents took into account the regulation of acidity within the molecular sieve channels, resulting in some small molecule hydrocarbons being unable to undergo deep transformation through the confinement effect of the molecular sieve channels. Summary of the Invention

[0008] The purpose of this invention is to overcome the problems of existing solid acid catalysts having fewer strong acid centers and more dispersed acid distribution, resulting in lower conversion rates for complex feedstocks. This invention provides a solid acid catalyst, its preparation method, and its applications. The solid acid catalyst of this invention features concentrated strong acid distribution and selective hydrogenation capabilities. When used in the aromatic conversion reaction of complex hydrocarbon feedstocks, this catalyst exhibits high reactivity and high product selectivity.

[0009] To achieve the above objectives, the present invention provides a solid acid catalyst, wherein the catalyst contains a high-valence metal-modified silica-alumina molecular sieve, a metal active component, and sulfate ions; the high-valence metal is selected from metals with a valence of +2 or higher; and the metal active component is selected from at least one of Group IIIA, IVB, VB, VIB, VIIB, and VIII metal elements.

[0010] In the catalyst, the proportion of strong acid with a desorption temperature >400℃ to the total acid content is more than 60%, calculated based on the NH3-TPD desorption amount.

[0011] Preferably, in the catalyst, the proportion of strong acid with a desorption temperature >400°C to the total acid content is 60-90%, calculated based on the amount of NH3-TPD desorption.

[0012] A second aspect of this invention provides a method for preparing a solid acid catalyst, the method comprising the following steps:

[0013] (a) The silica-alumina molecular sieve was exchanged with an aqueous solution containing a high-valence metal compound to obtain a silica-alumina molecular sieve modified with a high-valence metal.

[0014] (b) Reacting the high-valence metal-modified silica-alumina molecular sieve with an aqueous solution of the metal active component compound;

[0015] (c) Introduce a sulfate-containing compound into the reaction product obtained in step (b) by impregnation;

[0016] The method further includes shaping and pre-calcining the reaction product obtained in step (b) before step (c); or, the method further includes shaping and calcining the reaction product obtained in step (c) after step (c).

[0017] The high-valence metal is selected from metals with a valence of +2 or higher; the active metal component is selected from at least one of the metal elements of Groups IIIA, IVB, VB, VIB, VIIB and VIII.

[0018] The third aspect of this invention provides the application of the solid acid catalyst described in the first aspect or the solid acid catalyst prepared by the preparation method described in the second aspect in the conversion of aromatics.

[0019] The beneficial effects of this invention include:

[0020] The solid acid catalyst provided by this invention uses high-valence metal-modified silica-alumina molecular sieves in combination with metal active components and sulfate ions, and has concentrated strong acid distribution characteristics and selective hydrogenation function. It is used for aromatic conversion reactions of complex hydrocarbon feedstocks and has the advantages of high reactivity and high product selectivity. Detailed Implementation

[0021] The endpoints and any values ​​of the ranges disclosed herein are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of the various ranges, the endpoint values ​​of the various ranges and individual point values, and individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed herein.

[0022] The first aspect of this invention provides a solid acid catalyst, the catalyst comprising a high-valence metal-modified silica-alumina molecular sieve, a metal active component, and sulfate ions; the high-valence metal is selected from metals with a valence of +2 or higher; the metal active component is selected from at least one of Group IIIA, IVB, VB, VIB, VIIB, and VIII metal elements;

[0023] In the catalyst, the proportion of strong acid with a desorption temperature >400℃ to the total acid content is more than 60%, calculated based on the NH3-TPD desorption amount.

[0024] According to the present invention, preferably, in the catalyst, the proportion of strong acid with a desorption temperature >400°C, calculated based on the amount of NH3-TPD desorption, is 60-90% of the total acid amount. This preferred embodiment can effectively improve the conversion efficiency of the reaction or reduce the reaction temperature, and is particularly suitable for promoting low-temperature liquid-phase reaction processes.

[0025] The amount of strong acid and total acid with a desorption temperature >400℃ described in this invention were determined by the NH3-TPD method.

[0026] According to the present invention, preferably, based on the total weight of the high-valence metal modified silica-alumina molecular sieve, the content of the high-valence metal is 0.01-2 wt%, preferably 0.1-1.5 wt%. For example, 0.01 wt%, 0.05 wt%, 0.1 wt%, 0.2 wt%, 0.3 wt%, 0.4 wt%, 0.5 wt%, 0.6 wt%, 0.7 wt%, 0.8 wt%, 0.9 wt%, 1 wt%, 1.1 wt%, 1.2 wt%, 1.3 wt%, 1.4 wt%, 1.5 wt%, 1.6 wt%, 1.7 wt%, 1.8 wt%, 1.9 wt%, 2 wt%, and any value within any range formed by any two of these values.

[0027] According to the present invention, preferably, based on the total weight of the catalyst, the content of the high-valence metal modified silica-alumina molecular sieve is 20-80% by weight, preferably 30-70% by weight; the content of the metal active component is 10-50% by weight, preferably 15-35% by weight; and the content of sulfate ions is 0.1-15% by weight, preferably 0.5-10% by weight.

[0028] The sum of all components in the solid acid catalyst of this invention is 100%.

[0029] The content of each component in the solid acid catalyst of this invention is calculated by combining ICP with the feed ratio.

[0030] The present invention has a wide range of selection for the silica-alumina molecular sieve. Preferably, the silica-alumina molecular sieve is selected from at least one of ZSM-5, MOR, Beta, Y, MCM-22, MCM-49 and MCM-41.

[0031] According to the present invention, preferably, the high-valence metal is selected from at least one of the group VIB, VIIB, VIII and lanthanide metals.

[0032] The present invention has a wide range of choices for the high-valence metals. Preferably, the high-valence metals are selected from at least one of Cr, Mo, W, Mn, Re, Co, Fe, Ni, La and Ce.

[0033] More preferably, the high-valence metal is selected from at least one of La, Ce, Pt, Pd, Ni, Co, and Cu, more preferably from at least two of La, Ce, Pt, Pd, Ni, Co, and Cu, more preferably from at least one of La and / or Ce and Pt, Pd, Ni, Co, and Cu, and particularly preferably La-Pt, La-Pd, or La-Co. Using this preferred embodiment, the synergistic effect between the bimetals can further enhance the protonic acid activity under reaction conditions, thereby further reducing the reaction temperature or increasing the reaction activity.

[0034] Preferably, the weight ratio of La to Pt, Pd or Co is 1:0.05-2, more preferably 1:0.1-1.5.

[0035] The present invention has a wide range of choices for the metal active component. Preferably, the metal active component is selected from at least one of Al, Ga, Ti, Zr, V, Mo, W, Cr, Mn, Re, Co, Fe and Ni.

[0036] More preferably, the active metal component is selected from at least one of Zr, Ti, Fe, and Al, and more preferably from Al and at least one of Zr, Ti, and Fe. This preferred embodiment can further increase the amount of strong acid on the catalyst's outer surface.

[0037] Preferably, the weight ratio of Al to at least one of Zr, Ti and Fe is 1:0.5-20, more preferably 1:1-15.

[0038] Al in the metal active component can function as both an active component and a binder. Preferably, the solid acid catalyst may also optionally contain a binder. This invention offers a wide range of options for the binder content, which can be selected based on the Al content in the metal active component. Those skilled in the art can make adaptive selections according to specific circumstances.

[0039] The present invention allows for a wide range of choices of the type of adhesive. Preferably, the adhesive is alumina and / or silicon dioxide.

[0040] A second aspect of this invention provides a method for preparing a solid acid catalyst, the method comprising the following steps:

[0041] (a) The silica-alumina molecular sieve was exchanged with an aqueous solution containing a high-valence metal compound to obtain a silica-alumina molecular sieve modified with a high-valence metal.

[0042] (b) Reacting the high-valence metal-modified silica-alumina molecular sieve with an aqueous solution of the metal active component compound;

[0043] (c) Introduce a sulfate-containing compound into the reaction product obtained in step (b) by impregnation;

[0044] The method further includes shaping and pre-calcining the reaction product obtained in step (b) before step (c); or, the method further includes shaping and calcining the reaction product obtained in step (c) after step (c).

[0045] The high-valence metal is selected from metals with a valence of +2 or higher; the active metal component is selected from at least one of the metal elements of Groups IIIA, IVB, VB, VIB, VIIB and VIII.

[0046] This invention first introduces high-valence metals into the pores of aluminosilicate molecular sieves through an exchange process, effectively enhancing the acid center strength within the micropores. Simultaneously, the shape-selective effect of the molecular sieve pores prevents the high-valence metals from being poisoned by large-molecule toxins in the raw materials during the reaction, thus improving catalyst stability. Then, further modification with metal active component compounds and sulfate-containing compounds ensures that the outer surface of the molecular sieve also exhibits strong acidity, further enhancing the catalyst's acidity and giving it a concentrated strong acid distribution characteristic.

[0047] According to the present invention, the amounts of the high-valence metal modified silica-alumina molecular sieve, the metal active component compound, and the sulfate-containing compound are such that, based on the total weight of the catalyst, the content of the high-valence metal modified silica-alumina molecular sieve is 20-80% by weight, the content of the metal active component is 10-50% by weight, and the content of sulfate ions is 0.1-15% by weight.

[0048] According to the present invention, preferably, the amounts of the high-valence metal modified silica-alumina molecular sieve, the metal active component compound, and the sulfate-containing compound are such that, based on the total weight of the catalyst, the content of the high-valence metal modified silica-alumina molecular sieve is 30-70% by weight, the content of the metal active component is 15-35% by weight, and the content of sulfate ions is 0.5-10% by weight.

[0049] According to the present invention, preferably, the amount of the high-valence metal is such that, based on the total weight of the high-valence metal-modified silica-alumina molecular sieve, the content of the high-valence metal is 0.01-2% by weight, preferably 0.1-1.5% by weight.

[0050] According to the present invention, preferably, the exchange conditions in step (a) include: a temperature of 20-100°C, more preferably 30-90°C; and a time of 2-20 hours, more preferably 4-15 hours. This preferred embodiment can effectively control the content of high-valence metals in the silica-alumina molecular sieve.

[0051] According to the present invention, preferably, the high-valence metal is selected from at least one of the group VIB, VIIB, VIII and lanthanide metals.

[0052] According to the present invention, preferably, the high-valence metal is selected from at least one of La, Ce, Pt, Pd, Ni, Co and Cu, more preferably from at least two of La, Ce, Pt, Pd, Ni, Co and Cu, more preferably from at least one of La and / or Ce and Pt, Pd, Ni, Co and Cu, and particularly preferably La-Pt, La-Pd or La-Co.

[0053] According to the present invention, preferably, the amount of the La-containing compound, Pt, Pd or Co-containing compound is such that the weight ratio of La to Pt, Pd or Co in the high-valence metal modified silica-alumina molecular sieve is 1:0.05-2, preferably 1:0.1-1.5.

[0054] In this invention, the exchange described in step (a) can be performed once or multiple times. This invention does not have any particular limitation on this, as long as the content of high-valence metals in the silicon-aluminum molecular sieve modified with high-valence metals is within the above-mentioned range.

[0055] In this invention, when two or more high-valence metals are present during the exchange described in step (a), co-exchange or step-by-step exchange can be performed. Step-by-step exchange is preferred in this invention.

[0056] According to a specific embodiment of the present invention, step (a) first involves the exchange of La high-valence metals, followed by the exchange of Pt, Pd, or Co high-valence metals.

[0057] Preferably, the method further includes a filtration and washing operation after the high-value metal exchange is completed. The filtration and washing methods can be performed under conventional conditions, and will not be described in detail here.

[0058] Preferably, the method further includes performing ammonia exchange during the exchange process described in step (a).

[0059] The ammonia exchange described in this invention can be performed together with the first metal, or it can be performed after the first metal exchange is completed.

[0060] The present invention does not impose any particular limitation on the conditions for ammonia exchange, and can refer to the methods commonly used in the art. The present invention will not elaborate further here.

[0061] The present invention has a wide range of choices for the high-valence metal compound, as long as a high-valence metal can be provided. Preferably, the high-valence metal compound is a soluble salt of a high-valence metal, and is preferably selected from at least one of lanthanum nitrate, cobalt nitrate, and dichlorotetramineplatinum and dichlorotetraminepalladium.

[0062] When using dichlorotetraammineplatinum as a high-valence metal compound for exchange, the present invention preferably adds ammonia water to inhibit the decomposition of platinum ammonium salt.

[0063] This invention does not have a particular limitation on the amount of ammonia used, but the pH of the dichlorotetraammineplatinum aqueous solution is based on 8-11.

[0064] According to the present invention, preferably, the silica-alumina molecular sieve is selected from at least one of ZSM-5, MOR, Beta, Y, MCM-22, MCM-49, and MCM-41. The silica-alumina molecular sieve used in the present invention can be commercially available or prepared by conventional methods.

[0065] Preferably, the silica-alumina molecular sieve is of sodium or ammonia type.

[0066] According to the present invention, preferably, the reaction conditions in step (b) include: a temperature of 60-140°C, preferably 70-130°C; a time of 1-20 h, preferably 2-15 h; and a pH of 7-11, preferably 8-10.

[0067] Preferably, the reaction is carried out under stirring conditions. The present invention does not particularly limit the stirring speed and time; preferably, the stirring speed is 50-200 r / min.

[0068] Preferably, the pH in step (b) is adjusted using an alkali.

[0069] The present invention allows for a wide range of choices for the alkali, which can be any alkali commonly used in the art. Preferably, the alkali is an organic alkali and / or an inorganic alkali, more preferably selected from at least one of sodium hydroxide, potassium hydroxide, sodium bicarbonate, and ammonia, and more preferably ammonia.

[0070] The present invention has a wide range of choices for the metal active component. Preferably, the metal active component is selected from at least one of Al, Ga, Ti, Zr, V, Mo, W, Cr, Mn, Re, Co, Fe and Ni.

[0071] More preferably, the active metal component is selected from at least one of Zr, Ti, Fe and Al, and more preferably from Al and at least one of Zr, Ti and Fe.

[0072] According to the present invention, preferably, the amount of the Al-containing compound and the amount of at least one compound containing Zr, Ti and Fe is such that the weight ratio of Al to at least one of Zr, Ti and Fe in the prepared solid acid catalyst is 1:0.5-20, preferably 1:1-15.

[0073] According to the present invention, preferably, the metal active component compound is selected from at least one of Zr(NO3)4, ZrOCl2, Zr(SO4)2, Fe(NO)3, Fe2(SO4)3, TiCl4, Ti(SO4)2, Al(NO3)3, Al(OH)3, and Al2(SO4)3. All of the above substances are conventional choices in the art and are commercially available.

[0074] The first metal active component compound of the present invention may or may not contain water of crystallization, and the present invention does not limit this.

[0075] Preferably, the reaction products of step (b) or step (c) are dried independently to obtain their solid products. The drying conditions can be carried out under conventional conditions, which will not be described in detail here.

[0076] In this invention, there are no specific limitations on the method for introducing the sulfate-containing compound; conventional techniques in the art can be used. The impregnation method is preferred in this invention. The impregnation method includes: impregnating the solid product obtained in step (b) with an impregnation solution containing the sulfate-containing compound, and then drying it. The drying conditions can be carried out under conventional conditions, which will not be elaborated further here.

[0077] The present invention does not have a particular limitation on the number of impregnations, as long as the sulfate content in the obtained catalyst is within the above range.

[0078] Preferably, an optional roasting can be performed after each impregnation (under the same conditions as described below).

[0079] The present invention allows for a wide range of selection for the sulfate-containing compounds, as long as they contain sulfate. Preferably, the sulfate-containing compound is selected from at least one of sulfuric acid, ammonium sulfate, and ammonium bisulfate.

[0080] According to the present invention, preferably, the molding of the solid products obtained in steps (b) and (c) each independently comprises: kneading the solid product obtained in step (b) or (c) along with optional adhesive solvent and pore-forming agent in the presence of a solvent.

[0081] According to the present invention, preferably, the solvent is an organic solvent and / or water, more preferably water.

[0082] In this invention, unless otherwise specified, "optional" means containing or not containing, adding or not adding, or using or not using. Specifically, the molding process of this invention may or may not include adhesive solvents and pore-forming agents.

[0083] When an aluminum-containing compound (which can be a binder precursor or a metal active component compound) is added during the catalyst preparation process, the molding process also preferably involves the addition of a binder solvent.

[0084] The present invention allows for a wide range of choices of the adhesive solvent, including various adhesive solvents conventionally used in the art. According to the present invention, preferably, the adhesive solvent is an inorganic acid, more preferably nitric acid.

[0085] In a preferred embodiment, the adhesive solvent of the present invention is provided in the form of an aqueous solution. The present invention does not particularly limit the amount of the aqueous solution of the adhesive solvent, and it can be appropriately selected according to specific circumstances.

[0086] Preferably, the pore-forming agent is selected from at least one of styrax powder, polyethylene glycol, polystyrene, and carbon black.

[0087] Al in the metallic active component can function as both an active component and a binder. Preferably, a binder precursor can be optionally added during the molding process. This invention offers a wide range of options for the amount of binder precursor, which can be selected based on the Al content in the metallic active component of the prepared composite solid acid catalyst. Those skilled in the art can make adaptive selections according to specific circumstances.

[0088] Preferably, the binder precursor is boehmite and / or silica sol.

[0089] The present invention does not particularly limit the molding process, and it can be carried out according to conventional molding methods in the art. For example, it can be, but is not limited to, extrusion molding, spray molding, or compression molding. Extrusion molding is preferred in the present invention, and the specific method is well known to those skilled in the art, and will not be described in detail here.

[0090] According to the present invention, preferably, the pre-calcination conditions include: a temperature of 200-600℃, more preferably 300-550℃; and a time of 1-10h, more preferably 2-6h. The pre-calcination is generally carried out in an air atmosphere, which may include a flowing atmosphere or a stationary atmosphere.

[0091] The present invention does not impose any particular limitation on the roasting process, and can refer to methods commonly used in the art. Preferably, the roasting conditions include: a temperature of 500-650℃, more preferably 520-620℃; and a time of 1-10 hours, more preferably 2-6 hours. The roasting is generally carried out in an air atmosphere, which may include a flowing atmosphere or a stationary atmosphere.

[0092] According to a specific embodiment of the present invention, when molding the solid product obtained in step (c), the method further includes pre-calcining the solid product obtained in step (b) under the same conditions as described above.

[0093] According to a specific embodiment of the present invention, when molding the solid product obtained in step (b), the method further includes calcining the solid product obtained in step (c) (under the same conditions as described above).

[0094] The third aspect of this invention provides the application of the solid acid catalyst described in the first aspect or the solid acid catalyst prepared by the preparation method described in the second aspect in the conversion of aromatics, preferably in the application of xylene isomerization, toluene disproportionation and alkyl transfer or hydrogenation cracking of polycyclic aromatic hydrocarbons.

[0095] The solid acid catalyst described in this invention is applied to the aromatic conversion reaction of complex hydrocarbon feedstocks, especially to xylene isomerization, toluene disproportionation and alkyl transfer or hydrogenation cracking of polycyclic aromatic hydrocarbons, and has the advantages of high reactivity and high product selectivity.

[0096] According to the present invention, preferably, the reaction conditions include: a temperature of 100-500°C, more preferably 200-450°C; a pressure of 1-8 MPa, more preferably 2-6 MPa; a hydrogen-to-hydrocarbon molar ratio of 0.1-10, more preferably 0.2-8; and a liquid feedstock weight hourly space velocity of 0.5-10 h⁻¹. -1 Preferably 1-8h -1 .

[0097] According to the present invention, preferably, the catalyst is subjected to reduction treatment in a hydrogen atmosphere before the reaction, the reduction temperature is 300-500°C, the gas-solid volume ratio is 500-5000, and the reduction time is 1-6 hours.

[0098] The present invention will be described in detail below through embodiments.

[0099] In the following embodiments, the specific methods for each parameter are as described above;

[0100] The SiO2 / Al2O3 ratio of the mordenite is 26;

[0101] The SiO2 / Al2O3 ratio of the Beta zeolite is 35;

[0102] The SiO2 / Al2O3 ratio of the Y zeolite is 10;

[0103] The reagents used in the following examples are all commercially available and of analytical grade.

[0104] Example 1

[0105] (1) Weigh 15g of La(NO3)3·6H2O and dissolve it in 500g of water. Add 100g of sodium mordenite and exchange at 90℃ for 4h. Filter and wash. Redisperse the filter cake in a 10% (by weight) ammonium nitrate aqueous solution and exchange at 90℃ for 4h. Filter and wash to obtain La-MOR molecular sieve. Weigh 1g of dichlorotetraammineplatinum (molecular weight 334) and dissolve it in 500g of water. Add appropriate ammonia to adjust the pH to 8-9. Add La-MOR molecular sieve and exchange at 90℃ for 4h. Filter and wash to obtain high-valence metal modified molecular sieve (high-valence metal content is shown in Table 1).

[0106] (2) Weigh 150g ZrOCl2·8H2O and dissolve it in water. Add the high-valence metal modified molecular sieve obtained in step (1), and purify the solution with ammonia water to adjust the pH to 9. Stir at 150r / min at 110℃ for 10h and then discharge the material. Then dry to obtain the solid product.

[0107] (3) The solid product obtained in step (2) is pre-calcined at 300°C for 4 hours to obtain the catalyst blank.

[0108] (4) The catalyst preform was impregnated with 1 mol / L sulfuric acid solution for 1 h, dried at 120 °C, and 90 g of catalyst preform was weighed and mixed with 5 g of Tianqing powder and 30 g of pseudoboehmite. Then, an appropriate amount of dilute nitric acid solution was added and kneaded, extruded into strips, and then calcined at 550 °C for 4 h to obtain a solid acid catalyst. The catalyst composition is shown in Table 1.

[0109] Example 2

[0110] (1) Weigh 20g La(NO3)3·6H2O and 25g ammonium nitrate and dissolve them in 500g water. Add 100g sodium-type Beta zeolite and exchange at 90℃ for 4h. Filter and repeat the exchange twice. Wash to obtain La-Beta molecular sieve. Weigh 12g Co(NO3)2·6H2O and dissolve it in water. Add La-Beta molecular sieve and exchange at 90℃ for 4h. Filter and wash to obtain molecular sieve modified with high-valence metals (the content of high-valence metals is shown in Table 1).

[0111] (2) Weigh 70g ZrOCl2·8H2O and 50g aluminum nitrate and dissolve them in water. Add the high-valence metal modified molecular sieve obtained in step (1), and purge ammonia water to adjust the pH of the solution to 9. Stir at 150r / min at 110℃ for 10h and then discharge the material. Then dry to obtain a solid product.

[0112] (3) Weigh 90g of the solid product obtained in step (2), mix it with 5g of Tianqing powder and 30g of pseudoboehmite, add an appropriate amount of dilute nitric acid solution, knead, extrude into strips, and then pre-calcine at 300℃ for 4h to obtain the catalyst blank.

[0113] (4) The catalyst blank was impregnated with 1 mol / L sulfuric acid solution for 2 h, dried at 120 °C, and then calcined at 610 °C for 4 h to obtain a solid acid catalyst. The catalyst composition is shown in Table 1.

[0114] Example 3

[0115] (1) Weigh 25g Ce(NO3)3 and dissolve it in 500g water. Add 100g ammonium-type Beta zeolite and exchange at 60℃ for 4h. Filter and repeat the exchange twice. Wash to obtain Ce-Beta molecular sieve. Weigh 1g dichlorotetraamminepalladium and dissolve it in 500g water. Add appropriate ammonia to adjust the pH to 9. Add Ce-Beta molecular sieve and exchange at 60℃ for 4h. Filter and repeat the exchange twice. Wash to obtain molecular sieve modified with high-valence metals (the content of high-valence metals is shown in Table 1).

[0116] (2) Weigh 90g Fe2(SO4)3 and 20g aluminum nitrate and dissolve them in water. Add the high-valence metal modified molecular sieve obtained in step (1), and purge ammonia water to adjust the pH of the solution to 10. Stir at 90℃ and 150r / min for 4h, then discharge the material and dry it to obtain a solid product.

[0117] (3) Weigh 90g of the solid product obtained in step (2), mix it with 3g of Tianqing powder and 40g of pseudoboehmite, add an appropriate amount of dilute nitric acid solution, knead, extrude into strips, and then pre-calcine at 400℃ for 4h to obtain the catalyst blank.

[0118] (4) The catalyst blank was impregnated with 1 mol / L sulfuric acid solution for 0.5 h, dried at 120 °C, and then impregnated again once. Finally, it was calcined at 580 °C for 4 h to obtain a solid acid catalyst. The catalyst composition is shown in Table 1.

[0119] Example 4

[0120] (1) Weigh 15g of La(NO3)3·6H2O and dissolve it in 500g of water. Add 100g of ammonium-type Y zeolite and exchange at 35℃ for 6h. Filter and repeat the exchange twice. Wash to obtain La-Y molecular sieve. Weigh 2g of dichlorotetraammineplatinum and dissolve it in 500g of water. Add La-Y molecular sieve and exchange at 60℃ for 4h. Filter and repeat the exchange twice. Wash to obtain molecular sieve modified with high-valence metals (the content of high-valence metals is shown in Table 1).

[0121] (2) Weigh 200g Fe2(SO4)3 and 50g aluminum nitrate and dissolve them in water. Add the high-valence metal modified molecular sieve obtained in step (1), and purge ammonia water to adjust the pH of the solution to 10. Stir at 90℃ and 150r / min for 4h, then discharge the material and dry it to obtain a solid product.

[0122] (3) Weigh 90g of the solid product obtained in step (2), mix it with 3g of Tianqing powder and 60g of pseudoboehmite, add an appropriate amount of dilute nitric acid solution, knead, extrude into strips, and then pre-calcine at 450℃ for 4h to obtain the catalyst blank.

[0123] (4) The catalyst blank was impregnated with 1 mol / L ammonium sulfate solution for 0.5 h, calcined at 500 °C for 3 h, and then impregnated again once. Finally, it was calcined at 610 °C for 4 h to obtain a solid acid catalyst. The catalyst composition is shown in Table 1.

[0124] Example 5

[0125] The method of Example 2 was followed, except that the exchange of La(NO3)3·6H2O was not performed in step (1).

[0126] Comparative Example 1

[0127] (1) Weigh 90g ZrOCl2·8H2O and dissolve it in water. Add 100g ammonium type Beta zeolite, and purge ammonia water to adjust the pH of the solution to 9. Heat the solution to 110℃ and stir at a rate of 150r / min for 10h before discharging. Then dry the solution to obtain a solid product.

[0128] (2) Weigh 90g of the solid product obtained in step (1), mix it with 5g of Tianqing powder and 30g of pseudoboehmite, add an appropriate amount of dilute nitric acid solution, knead, and extrude into strips. Pre-calcine at 300℃ for 4h to obtain the catalyst blank.

[0129] (3) The catalyst blank was impregnated with 1 mol / L sulfuric acid solution for 1 h, dried at 120 °C, and then calcined at 610 °C for 4 h to obtain a solid acid catalyst. The catalyst composition is shown in Table 1.

[0130] Table 1

[0131]

[0132] Test Example 1

[0133] Weigh 5g of catalyst and load it into a fixed-bed reactor. Introduce hydrogen at a rate of 80mL / min, pressurize to 4MPa, heat to 450℃ and hold at that temperature for 3 hours. Then cool to 290℃ and, after the temperature stabilizes, introduce a mixture of reformed toluene and C9+A (reformed toluene and C9+A) at a rate of 10g / h. + A has a weight ratio of 1 / 1), in which the reformed toluene has the following weight composition: non-aromatic hydrocarbons: 5%, toluene: 95%; C9 + The composition of A by weight is: ethylbenzene: 25%, trimethylbenzene: 55%, tetramethylbenzene: 9%, dimethylethylbenzene: 7%, others: 4%. The results after 10 hours of reaction are shown in Table 2.

[0134] Table 2

[0135]

[0136]

[0137] As can be seen from the results in Table 2, the use of the acid catalyst of the present invention to treat complex hydrocarbon raw materials has a high reactant conversion rate and product selectivity, and can obtain a high purity of benzene product. It has a significantly better effect under low temperature reaction conditions.

[0138] The preferred embodiments of the present invention have been described in detail above; however, the present invention is not limited thereto. Within the scope of the inventive concept, various simple modifications can be made to the technical solutions of the present invention, including combinations of various technical features in any other suitable manner. These simple modifications and combinations should also be considered as the content disclosed in the present invention and are all within the protection scope of the present invention.

Claims

1. A solid acid catalyst, characterized in that, The catalyst contains a silica-alumina molecular sieve modified with a high-valence metal, a metal active component, and sulfate ions; the high-valence metal is selected from at least one of Cr, Mo, W, Mn, Re, Co, Fe, Ni, Pt, Pd, La, Ce, and Cu; the metal active component is selected from at least one of Al, Ga, Ti, Zr, V, Mo, W, Cr, Mn, Re, Co, Fe, and Ni. In the catalyst, the proportion of strong acid with a desorption temperature >400℃ to the total acid content is more than 60%, calculated based on the NH3-TPD desorption amount. Based on the total weight of the catalyst, the content of high-valence metal-modified silica-alumina molecular sieve is 20-80% by weight; the content of metal active component is 10-50% by weight; and the content of sulfate ion is 0.1-15% by weight.

2. The catalyst according to claim 1, wherein, In the catalyst, the proportion of strong acids with a desorption temperature >400℃ to the total acid content is 60-90%, calculated based on the NH3-TPD desorption amount.

3. The catalyst according to claim 1, wherein, Based on the total weight of the silica-alumina molecular sieve modified with high-valence metals, the content of high-valence metals is 0.01-2% by weight.

4. The catalyst according to claim 3, wherein, Based on the total weight of the silica-alumina molecular sieve modified with high-valence metals, the content of high-valence metals is 0.1-1.5% by weight.

5. The catalyst according to claim 1, wherein, Based on the total weight of the catalyst, the content of high-valence metal-modified silica-alumina molecular sieve is 30-70% by weight; the content of metal active component is 15-35% by weight; and the content of sulfate ion is 0.5-10% by weight.

6. The catalyst according to claim 1, wherein, The silicon-aluminum molecules are selected from at least one of ZSM-5, MOR, Beta, Y, MCM-22, MCM-49, and MCM-41.

7. The catalyst according to claim 1, wherein, The high-valence metal is selected from at least one of La, Ce, Pt, Pd, Ni, Co, and Cu.

8. The catalyst according to claim 7, wherein, The high-valence metal is selected from at least two of La, Ce, Pt, Pd, Ni, Co, and Cu.

9. The catalyst according to claim 8, wherein, The high-valence metal is La-Pt, La-Pd, or La-Co.

10. The catalyst according to claim 1, wherein, The active metal component is selected from at least one of Zr, Ti, Fe and Al.

11. The catalyst according to claim 10, wherein, The active metal component is selected from at least one of Al, Zr, Ti, and Fe.

12. A method for preparing the solid acid catalyst according to any one of claims 1-11, the method comprising the following steps: (a) The silica-alumina molecular sieve is exchanged with an aqueous solution containing a high-valence metal compound to obtain a silica-alumina molecular sieve modified with a high-valence metal; (b) Reacting the high-valence metal-modified silica-alumina molecular sieve with an aqueous solution of the metal active component compound; (c) Introducing a sulfate-containing compound into the solid product obtained in step (b) by impregnation; The method further includes, before step (c), shaping and pre-calcining the solid product obtained in step (b); or, the method further includes, after step (c), shaping and calcining the solid product obtained in step (c).

13. The method according to claim 12, wherein, The amounts of the high-valence metal-modified silica-alumina molecular sieve, the metal active component compound, and the sulfate-containing compound are such that, based on the total weight of the catalyst, the content of the high-valence metal-modified silica-alumina molecular sieve is 30-70% by weight, the content of the metal active component is 15-35% by weight, and the content of sulfate ions is 0.5-10% by weight.

14. The method according to claim 12, wherein, The amount of the high-valence metal used is such that, based on the total weight of the high-valence metal-modified silica-alumina molecular sieve, the content of the high-valence metal is 0.01-2% by weight.

15. The method according to claim 14, wherein, The amount of the high-valence metal used is such that, based on the total weight of the high-valence metal-modified silica-alumina molecular sieve, the content of the high-valence metal is 0.1-1.5% by weight.

16. The method according to claim 12, wherein, The conditions for the exchange in step (a) include: a temperature of 20-100℃ and a time of 2-20h.

17. The method according to claim 16, wherein, The conditions for the exchange in step (a) include: a temperature of 30-90°C and a time of 4-15 hours.

18. The method according to claim 12, wherein, The silicon-aluminum molecules are selected from at least one of ZSM-5, MOR, Beta, Y, MCM-22, MCM-49, and MCM-41.

19. The method according to claim 12, wherein, The reaction conditions in step (b) include: temperature of 60-140℃; time of 1-20h; and pH of 7-11.

20. The method according to claim 19, wherein, The reaction conditions in step (b) include: a temperature of 70-130°C; a time of 2-15 h; and a pH of 8-10.

21. The method according to claim 12, wherein, The active metal component is selected from at least one of Zr, Ti, Fe and Al.

22. The method according to claim 21, wherein, The active metal component is selected from at least one of Al, Zr, Ti, and Fe.

23. The method according to claim 22, wherein, The active metal component compound is selected from at least one of Zr(NO3)4, ZrOCl2, Zr(SO4)2, Fe(NO)3, FeSO4, TiCl4, Ti(SO4)2, Al(NO3)3, Al(OH)3 and Al2(SO4)3.

24. The method according to any one of claims 12-23, wherein, The sulfate-containing compound is selected from at least one of sulfuric acid, ammonium sulfate, and ammonium bisulfate.

25. The method according to any one of claims 12-23, wherein, The pre-calcination conditions include: a temperature of 200-600℃ and a time of 1-10 hours; The roasting conditions include: a temperature of 500-650℃ and a time of 1-10h.

26. The method of claim 25, wherein, The pre-calcination conditions include: a temperature of 300-550℃ and a time of 2-6 hours; The roasting conditions include: a temperature of 520-620℃ and a time of 2-6 hours.

27. The application of a solid acid catalyst according to any one of claims 1-11 or a solid acid catalyst prepared by any one of claims 12-26 in the conversion of aromatics.

28. The application according to claim 27, wherein, The solid acid catalyst is used in xylene isomerization, toluene disproportionation and alkyl transfer or hydrogenation cracking of polycyclic aromatic hydrocarbons.

29. The application according to claim 27, wherein, The reaction conditions include: temperature of 100-500℃; pressure of 1-8 MPa; hydrogen-to-hydrogen molar ratio of 0.1-10; and liquid feedstock weight hourly space velocity of 0.5-10 h⁻¹. -1 .

30. The application according to claim 29, wherein, The reaction conditions include: a temperature of 200-450℃; a pressure of 2-6 MPa; a hydrogen-to-hydrocarbon molar ratio of 0.2-8; and a liquid feedstock weight hourly space velocity of 1-8 h⁻¹. -1 .

Citation Information

Patent Citations

  • Preparation method of molecular sieve catalyst with superpower acidity

    CN101209423A

  • Rare-earth-containing Y type molecular sieve cracking catalyst and method for preparing same

    CN102806097B

  • Isomerization catalyst composition and application thereof

    CN103041843A

  • Magnesium modified ultrastable rare earth Y-type molecular sieve and preparation method thereof

    CN103159227B

  • A modified β-molecular sieve, its preparation method and application

    CN108328624B